Extracellular Vesicles From Auditory Cells as Nanocarriers for Anti-inflammatory Drugs and Pro-resolving Mediators - Kalinec, Gilda M.; Gao, Lucy; Cohn, Whitaker; Whitelegge, Julian P.; Faull, Kym F.; Kalinec, Federico (Frontiers in Cellular Neuroscience, 2019)
Drug- and noise-related hearing loss are both associated with inflammatory responses in the inner ear. We propose that intracochlear delivery of a combination of pro-resolving mediators, specialized proteins and lipids that accelerate the return to homeostasis by modifying the immune response rather than by inhibiting inflammation, might have a profound effect on the prevention of sensorineural hearing loss. However, intracochlear delivery of such agents requires a reliable and effective method to convey them, fully active, directly to the target cells. The present study provides evidence that extracellular vesicles (EVs) from auditory HEI-OC1 cells may incorporate significant quantities of anti-inflammatory drugs, pro-resolving mediators and their polyunsaturated fatty acid precursors as cargo, and potentially could work as carriers for their intracochlear delivery. EVs generated by HEI-OC1 cells were divided by size into two fractions, small (≤150 nm diameter) and large (>150 nm diameter), and loaded with aspirin, lipoxin A4, resolvin D1, and the polyunsaturated fatty acids (PUFA) arachidonic, eicosapentaenoic, docosahexanoic, and linoleic. Bottom-up proteomics revealed a differential distribution of selected proteins between small and large vesicles. Only 17.4% of these proteins were present in both fractions, whereas 61.5% were unique to smaller vesicles and only 3.7% were exclusively found in the larger ones. Importantly, the pro-resolving protein mediators Annexin A1 and Galectins 1 and 3 were only detected in small vesicles. Lipidomic studies, on the other hand, showed that small vesicles contained higher levels of eicosanoids than large ones and, although all of them incorporated the drugs and molecules investigated, small vesicles were more efficiently loaded with PUFA and the large ones with aspirin, LXA4 and resolvin D1. Importantly, our data indicate that the vesicles contain all necessary enzymatic components for the de novo generation of eicosanoids from fatty acid precursors, including pro-inflammatory agents, suggesting that their cargo should be carefully tailored to avoid interference with their therapeutic purpose. Altogether, these results support the idea that both small and large EVs from auditory HEI-OC1 cells could be used as nanocarriers for anti-inflammatory drugs and pro-resolving mediators.